2018
DOI: 10.1080/21642583.2018.1509400
|View full text |Cite
|
Sign up to set email alerts
|

Position feedback dynamic surface control for pneumatic actuator position servo system

Abstract: Pneumatic servo system is widely utilized in many industries, which has huge potential to replace hydraulic and electromechanical system due to its low-cost, high power quality ratio and quick response. There have been considerable control methods proposed to complete pneumatic position servo control. However, these methods still have some inevitable problems which remain to be settled. In this paper, a position feedback dynamic surface control is applied to the pneumatic system based on our pneumatic actuator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Actuation in exoskeletons should have a fast and accurate response (Rigatos et al , 2023a; Cao et al , 2018; Varghese et al , 2012; Cao and Huang, 2020). Although electric motors come against high mechanical impedance and the risk of causing injuries, pneumatic actuators exhibit forces and torques which stay within moderate variation ranges (Hoang et al , 2020; Hilderbrandt et al , 2010; Liu et al , 2018). Besides, unlike direct current electric motors, pneumatic actuators have an improved weight-to-power ratio and avoid overheating problems (Dong et al , 2021; Sasaki and Kawashima, 2008; Zilic et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Actuation in exoskeletons should have a fast and accurate response (Rigatos et al , 2023a; Cao et al , 2018; Varghese et al , 2012; Cao and Huang, 2020). Although electric motors come against high mechanical impedance and the risk of causing injuries, pneumatic actuators exhibit forces and torques which stay within moderate variation ranges (Hoang et al , 2020; Hilderbrandt et al , 2010; Liu et al , 2018). Besides, unlike direct current electric motors, pneumatic actuators have an improved weight-to-power ratio and avoid overheating problems (Dong et al , 2021; Sasaki and Kawashima, 2008; Zilic et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Further detail about friction models was given by Keck et al (2017) and Liang et al (2012). When the literature is examined, it is observed that generally Coulomb-viscous (Lin et al, 2018; Wang et al, 2004), Stribeck (Kosari and Moosavian, 2015; Nouri, 2004), or LuGre (Tran and Yanada, 2013) models are mainly preferred in pneumatic cylinders. Among these models, more enhanced and complex one is the LuGre model, where this model can identify the friction characteristics of the cylinder even under pre-sliding region as well.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumatic servo systems have the potential to replace hydraulic and electromechanical systems. Lin et al [11] applied position feedback dynamic surface control to pneumatic systems and developed an improved dynamic surface controller to overcome model uncertainty, external disturbances, and noise interference; they verified through experiments that the proposed control method exhibited more advantages than traditional proportional-integral-derivative (PID) controllers. Zhang et al [12] proposed an accurate model for a valve controlled pneumatic rotary actuator servo system.…”
Section: Introductionmentioning
confidence: 99%